Pengaruh literasi dan pendapatan terhadap keputusan berwakaf uang melalui LKS-PWU di Kota Surabaya - Fatkhan, Fatkhan; Anwar , Moch. Khoirul (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The purpose of this study was to determine the effect of literacy and income levels on cash waqf decisions at islamic financial institutions receiving cash waqf in the city of surabaya. The independent variable in this study consisted of 2 variables, namely literacy and income, while the dependent variable in this study was the decision to endow cash in lks-pwu. This study uses a quantitative method with a sample of 100 respondents. The questionnaire was distributed using right and wrong answers according to the guidelines of the indonesian waqf board ilw in measuring literacy levels. While the statements for other variables use a likert scale. The results of this study indicate that the literacy variable has an effect on the cash waqf decision variable in lks-pwu surabaya city. In addition, the income variable also affects the cash waqf decision variable in lks-pwu. The results of the coefficient of determination test (r square) show that literacy and income variables have a simultaneous effect of 37.7% on the decision to endow cash in lks-pwu.